Elementos para una ganadería ecológica en el municipio de Sucre (Cauca) (2017)
This book is a tool for all agricultural workers (especially those in the municipality of Sucre). It exalts the knowledge that is needed about water, land and the plant-animal relationship to carry out good agricultural and livestock practices. They will know what silvopastoral systems are and the strategies they must do to get the best out of what they are producing on their land, in an ecological way and with the least possible impact on the environment.